Synthesis and structure of some α,β-unsaturated ketones from (4’-methyl-α-pyrono)[5’,6’-g](3-acetyl-4-methylcoumarin) - Thanh, Nguyễn Ngọc; Hảo, Nguyễn Minh; Phong, Nguyễn Thị Thanh (Vietnam Journal of Chemistry, 2012)
By cyclization reaction of 6-acetyl-7-hydroxy-4-methylcoumarin with ethyl acetoacetate to get (4’-methyl-a-pyrono[5’,6’-g](3-acetyl-4-methylcoumarin). The product was then transformed by condensation with aromatic aldehydes to form a series of new ¸,©-unsaturated ketones (10 compounds). The purity and structure of the obtained products were determined by thin layer chromatography, IR, 1H-NMR, 13C-NMR, HSQC, HMBC and MS spectroscopic data.